Analisis Pengaruh Sistem Akreditasi Terhadap Peningkatan Kualitas Pelayanan - Sambo, Sri Wahyuni; Amelia, Inneke Mutiara (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Accreditation system on improving the quality of services in the public sector, especially in health institutions in Indonesia. The SLR is used to examine the effect of the accreditation system on improving the quality of services in various sectors, such as health and education. The process includes determining research questions, inclusion and exclusion criteria, and analyzing data from relevant articles to understand the contribution of accreditation. The results of the study are expected to provide in-depth understanding and practical recommendations for institutions in implementing a more effective accreditation system. The results of this work emphasize the importance of the accreditation system in improving the quality of services through periodic external monitoring. Accreditation functions not only as an evaluation tool, but also as a coaching instrument to ensure compliance with established standards. This monitoring helps identify the weaknesses and strengths of the institution, so that improvements can be made systematically. Accredited institutions show improved performance in aspects of governance, operational efficiency, and patient safety, as well as better clinical trial results and increased levels of customer satisfaction. Overall, accreditation serves as a mechanism to maintain and improve the quality of services, providing direct benefits to the community using the services.